"I, astonished, discovered by chance the only specimen”: the first velvet worm (Onychophora) - Monge, Julián (Universidad de Costa Rica, 2019)
The first description of a velvet worm, misidentified as a slug with legs, was published in Latin by Lansdown Guilding in 1826, but apparently, no translation is available. Here, I present English and Spanish translations of that first description, and some biographical notes on Guilding.